(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research sought to reveal the degree of application of entrepreneurship education requirements in the graduate program at the College of Education, according to the opinion of faculty members, and differences were identified according to gender, department, academic rank, and years of experience. The research was applied to the entire sample, consisting of (53) faculty members at the College of Education, Tishreen University. The research followed the descriptive approach, and the research used a measure of the requirements for entrepreneurial education prepared by the researcher. The results showed that the level of application of entrepreneurial education requirements in the graduate program at the College of Education, according to the opinion of faculty members, was average in its overall degree and on both axes (legislative and administrative requirements, technical and human requirements). While the level of application of the financial and equipment requirements axis was low, it was also shown that there was no difference in the opinion of faculty members in the degree of availability of the requirements for entrepreneurial education in the graduate studies program according to the variables (gender and the department to which the teacher belongs), while it was found that there were differences between them according to academic rank in favor of the rank of professor. And an established teacher, and differences appeared between them according to years of experience in favor of years of experience exceeding six years.